2014
DOI: 10.1007/s00167-014-3064-8
|View full text |Cite
|
Sign up to set email alerts
|

Difference in knee rotation between total and unicompartmental knee arthroplasties during stair climbing

Abstract: Both UKA and TKA knees have shown overall similar knee kinematics, though UKA knee may allow greater degree of rotation freedom, which resembles normal knee kinematics during stair walking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
(46 reference statements)
1
11
0
Order By: Relevance
“…Furthermore, in most cases unnatural kneeling activities or simple level walking have been analyzed. In a study by Jung et al [ 52 ] similar to the current study’s transverse plane knee kinematics were reported in a TKA- and UKA-group during stair climbing, whereby the UKA-group was supposed to present knee motion closer to normal than the TKA-group. A healthy CG or the investigation of the non-op limb was not included.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, in most cases unnatural kneeling activities or simple level walking have been analyzed. In a study by Jung et al [ 52 ] similar to the current study’s transverse plane knee kinematics were reported in a TKA- and UKA-group during stair climbing, whereby the UKA-group was supposed to present knee motion closer to normal than the TKA-group. A healthy CG or the investigation of the non-op limb was not included.…”
Section: Discussionsupporting
confidence: 80%
“…investigated the difference during stair walking in patients with simultaneous TKA and UKA, and concluded that UKA knee might allow greater degree of rotation freedom, which resembled normal knee kinematics during stair walking. 22 In particular, UKA knees exhibited significantly greater degree of rotation in transverse planes, compared to TKA. However, in their study, peak tibial internal rotation moment in terminal stance phase was not evaluated.…”
Section: Discussionmentioning
confidence: 96%
“…Further potential reasons for normal knee kinematics and kinetics in UKA patients, such as the preservation of the lateral knee compartment or different bearing shapes compared with TKA, should be considered. Addressing the question of whether UKA is able to restore normal knee mechanics compared with TKA, UKA patients in a study by Jung et al [16] performed stair climbing with similar knee internal rotation in their operated knee to the non-operated knee (non-OP knee) in contrast to TKA patients. A recent study [17] used a machine learning approach to classify and identify UKA and TKA knees on the basis of recognized patterns.…”
Section: Introductionmentioning
confidence: 99%